Reconceiving Murdochian Realism - Cathy Mason (Ergo, An Open Access Journal of Philosophy, 2023)
It can be tempting to read Iris Murdoch as subscribing to the same position as standard contemporary moral realists. Her language is often similar to theirs and they share some key commitments, most importantly the rejection of the fact-value dichotomy. However, it is a mistake to assume that her realism amounts to the same thing theirs does. In this paper I offer a sketch of her alternative conception of realism, which centres on the idea that truth and reality are fundamentally ethical concepts. For Murdoch, I suggest, realism is a matter of doing justice to the objects one is confronted with—something that cannot be understood except in ethical terms.